EFFECT OF SOCIAL MEDIA WHATSAPP ON READING INTEREST OF TENTH GRADE STUDENTS OF SMA NEGERI 1 PENEBEL - Wayan Thia Cahyani; Made Wahyu Mahendra (Widyadewata, 2023)
The aim of this study was to find out the significant effect of social media WhatsApp on students’ reading interest at the tenth-grade students of SMA Negeri 1 Penebel in the academic year 2022/2023. In this study there were 32 students who taken as the sample and it determined using cluster random sampling technique. First, this sample used as control group taught using Google Classroom. Then, it used as experimental group taught using WhatsApp. The research method used in this study was a quantitative approach using pre-experimental design with type One Group Pretest-Posttest. The data collection is using questionnaires as pre-test and post-test in order to find out students’ English reading interest respectively. The data collection of students’ reading interest was carried out using 21 questionnaires as pre-test and post-test. It calculated with descriptive analysis and inferential analysis using SPSS version 26 for windows. The results of the study were the t-test obtained tcount > ttable obtained (5.668 > 0.3440). It means null hypothesis (H0) in this research is rejected and the alternative hypothesis (Ha) which stated there is significant effect of social media WhatsApp toward students’ reading interest is accepted. Thus, it can be concluded that there was a significant effect of social media WhatsApp toward students’ reading interest at tenth-grade students of SMA Negeri 1 Penebel.